Stylistic Analysis of Weeping Wisdom by Nazir Ahmed Shawl through the Lens of Leech’s (1969) and Short’s (1996) Models of Linguistic Deviation - Khan, Imran Ali; Amir, Fizza; Ur Rahman, Zohaib; Zubair, Muhammad (2024)
In this research, the researchers analyze Shawl's Weeping Wisdom through the lens of linguistic deviation. This poem includes semantic and morphological contradictions. The researchers explore how the writer put all the ideas coherently to describe his feelings about the sacrifices, loss, and uncertainty that a man faces during life. The poet also describes that life is fragile and that not all desires are meant to be fulfilled. The poem's speaker beautifully reflects his views by using different figurative devices. The researchers focus on Leech's model (1969) to explore different levels of semantic types and Short's (1996) model of linguistic deviation to find out how the writer of the poem deviation.